Integrasi Islamic Worldview dalam Ekonomi Indonesia: Perspektif Neoklasik, Institusional dan Makroekonomi - Setiawan, Dhannie Stephend (BUDAI: MULTIDISCIPLINARY JOURNAL OF ISLAMIC STUDIES, 2023)
The Indonesian economy, as one of the countries with the largest Muslim population in the world, is faced with various challenges in achieving inclusive and sustainable economic development. This article aims to examine how the Islamic worldview can be integrated into Indonesian economic analysis, by referring to three leading economic journals. The first approach taken is the neoclassical perspective in the Journal of Economics and Development, which examines fiscal and monetary policy. Within the framework of the Islamic worldview, this analysis needs to pay attention to the principles of social justice, avoidance of usury, and fair distribution of wealth. Second, in the Journal of Economics and Development Studies, the institutional economics approach highlights the importance of institutions in economic development. In the Islamic view, the principles of shura (deliberation) and amanah (trust) are the keys to institutional management that is oriented towards the welfare of the people. Third, in the Journal of Economic Sciences, globalization is analyzed in the context of its impact on the Indonesian economy. The Islamic worldview offers solutions to global inequality through social instruments such as zakat, infaq, and waqf. Overall, the integration of Islamic economic principles provides a new perspective that focuses more on social justice and shared prosperity, which can enrich Indonesia's economic policies in achieving sustainable and inclusive development.